Error analysis of English passive voice use among ninth-grade Vietnamese students - Ha, Hy Thuy Van; Duong, Tham My (Penerbit Universiti Kebangsaan Malaysia, 2024)
This research was conducted to scrutinise common errors of 9th graders in the use of English passive voice (EPV), which is a challenging aspect of learning English for most EFLL/ ESL learners. The participants were those who were learning at a secondary school in a Vietnamese rural region. The research analysed the EPV errors in 162 student tests, which include all EPV structures, namely simple passives with 'be', simple passives with 'get', complex passives with 'be', pseudo passives with 'get' or 'have', and stative passives. To better analyse the participants’ performance, the test is divided into two main sections: 18 closed-ended test items and one open-ended writing task. The research results showed that these learners made the most misformation errors in both sections of the test. On the other hand, all the other types of errors accounted for the same fraction in the open-ended task, while misorder errors were the least common category in the closed-ended test items. Specifically, omission and addition errors are mainly caused by the participants being careless with the auxiliary verb 'be'. In contrast, the misformation subcategories are much more diverse, with using completely wrong passive structures and wrong past participles being the predominant faults in closed-ended and open-ended sections, respectively.